HASIL PENELITIAN PENGARUH KECERDASAN DAN BUDAYA ETIS ORGANISASI TERHADAP PRILAKU ETIS AUDITOR DI PROVINSI BALI - Ni Luh Putu Normadewi Abdi Pradnyani; Ni Putu Riasning; Luh Kade Datrini (Faculty of Economics and Business, Universitas Warmadewa, 2018)
ABSTRACT The aim of this research is to explain the influence of Emotional Intelligence, Locus of Control and Ethical Culture of Organization to Ethical Behavior of Auditor in Bali Province. The research method is survey method. The data used consist of primary data and secondary data. This study used 65 respondents determined by using purposive sampling. This research uses multiple linear regression analysis techniques with simultaneous test and partial test with the program SPSS for window version 21. The result of the research with multiple regression test shows that by using simultaneous test of Emotional Intelligence, Locus of Control and Ethical Culture of Organization have positive and significant influence to Ethical Behavior of Auditor. And based on the partial test indicates that the variables of Emotional Intelligence, Locus of Control and Ethical Culture of Organization have a positive and significant influence to EthicalBehavior of Auditor in Bali Province Keywords: Emotional intelligence, Locus of control, Organization Ethical Culture and ethics.